Development of an internal locus of control scale for at-risk adolescents - Dewi, Annisa Dianesti; Dianesti, Nadia Puti; Saputra, Dian Erhan; Andre (Proceedings Academic Universitas Jambi, 2025)
Background: Locus of control is a key psychological construct that plays an important role in adolescents’ self-regulation and resilience, especially among at-risk groups who experience vulnerabilities in family, social, and academic domains. However, valid and reliable instruments to measure this construct remain limited in the Indonesian context. Objective: This study aims to develop and validate an Internal Locus of control Scale specifically designed for at-risk adolescents. Methods: A quantitative research design was employed with 260 participants identified as at-risk based on school counselor and parental recommendations. The initial pool of 29 items was subjected to content validity testing by seven raters, resulting in 14 items meeting the Aiken’s V ≥ 0.75 criterion. Subsequent Confirmatory Factor Analysis (CFA) supported the removal of two items with weak factor loadings, yielding a final 12-item unidimensional model. The scale demonstrated significant item-total correlations ranging from r = 0.447 to r = 0.639 (p < 0.001). CFA results indicated a good model fit (CFI = 0.959; TLI = 0.942; RMSEA = 0.0466, 90% CI [0.0242–0.0664]). Reliability analysis showed Cronbach’s Alpha of 0.805, reflecting high internal consistency. Results: These findings confirm that the Internal Locus of control Scale is psychometrically sound and suitable for assessing internal locus of control among at-risk adolescents. Conclusion: The scale can be used by researchers, psychologists, and counselors to support interventions aimed at strengthening adolescents’ self-regulation and adaptive coping in challenging environments.